HUBUNGAN ANTARA PENGETAHUAN PEREMPUAN USIA REPRODUKTIF (WRA) DENGAN PENGGUNAAN ALAT KONTRAKSEPSI INTRAUTERIN (IUD) DI KLINIK SEHATI PADA TAHUN 2024 - Ritonga, Juliana Safitri; Nazara, Titin Sundari; Sari, Siti Nurul Fadhilah; Rahayu, Widya (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The purpose of this study was to determine the relationship between the knowledge of women of childbearing age and the use of IUD contraceptives at the Sehati Clinic in Medan in 2024. This study used an analytical survey design with a cross-sectional approach. The sample in this study was women of childbearing age who used IUD contraceptives, with a total population of 30 people. The results of this study indicate that the majority of women of reproductive age have insufficient knowledge, with 12 individuals (40.0%) falling into this category. A minority of WRA, 6 individuals (20.0%), have adequate knowledge. The majority of WUS who used IUD contraceptives were 14 people (46.7%), and the minority of WUS who did not use IUD contraceptives were 16 people (53.3%). There is a relationship between the knowledge of women of reproductive age and the use of IUD contraceptives at the confidence level where the p-value is 0.004<0.05. Therefore, the conclusion of this study is that there is a relationship between the knowledge of women of reproductive age (WRA) and the use of IUD contraceptives at the Sehati Clinic in 2024. It is recommended that women of reproductive age (WRA) always participate in health education sessions provided by healthcare workers and seek more information about the effectiveness of IUD so that their knowledge can continue to improve.